Ukraine : First Review Under the Stand-By Arrangement, Requests for Extension and Rephasing of Access of the Arrangement, Waivers of Nonobservance of a Performance Criterion, Financing Assurances Review, and Monetary Policy Consultation-Press Release; Staff Report; and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report, 2021)
After a number of critical setbacks and delays in the 16 months since program approval, the authorities have taken important corrective actions to address shocks to program objectives. Early tension around the authorities' commitment to uphold the independence of the National Bank of Ukraine required a pause to assess policy continuity and to determine possible corrective actions. A prior action for this review and new commitments by the authorities provide a way forward in protecting a key policy pillar under the program. Similarly, adverse Constitutional Court rulings challenged the anticorruption framework in fundamental ways that required restoring its effectiveness before the review could proceed. In a push to make progress on delayed structural benchmarks, the authorities have recently met seven of the nine structural benchmarks set at the time of the program request.